Instilling trash throwing behavior through play in early childhood: a review - Lagu, Abdul Majid HR; Syafar, Muhammad; Thaha, Ridwan Mochtar; Razak, Amran (International Journal of Public Health Science (IJPHS), 2025)
The waste problem is a serious problem that affects the environment and human health. Involving young children in waste management is very important because they are the future generation. One effective method for instilling waste disposal behavior in young children is by providing educational games. This literature review aims to find out how to instill waste disposal behavior through games in early childhood. The method used is systematic review and meta-analysis (PRISMA). Based data obtained from Google Scholar, PubMed/NCBI, UpToDate, Springer, Wiley on Library, ScienceDirect, MedRxiv, DOAJ, MDPI, and JAMA Network. A total of 3,728 journals were found which were then filtered based on related titles and 1,400 journal titles were obtained. Next, selection was carried out based on research variables, where there were 764 journals that were excluded because there were no suitable variables, namely those related to instilling trash throwing behavior in children through games, so that the remaining 636 journals were then filtered based on the research method used. It was found that 444 journals did not use the method cross sectional study, cohort, experimental study, quasi experiment, and field research so that the remaining 192 journals were then filtered again based on journal access and journal indexes to obtain 14 journals.